Familial Creutzfeldt-Jakob disease in an Indian kindred - Sarosh M Katrak; Apoorva Pauranik; Shrinivas B Desai; Simon Mead; Jon Beck; Sebastian Brandner; John Collinge (Annals of Indian Academy of Neurology, 2019)
It is now known that the inherited prion disease is caused by over 60 different mutations in the Prion protein (PRNP) gene. Four missense mutations at codons 102, 178, 200 and 210, account for over 95% of these cases. In this study we describe, a large Indian family with familial Creutzfeldt Jakob Disease (fCJD). One affected member presented with a presenile dementia, a protracted clinical course and characateristic MRI features. Genetic analysis revealed a D178N mutation in the 2 affected individuals and 7 unaffected members. The neuropathological examination of the brain of one of the affected member was conspicuous by spongiform degeneration, neuronal loss and gliosis. This is a detailed report of a genetically and neuropathologically proven fCJD from India.